PENGARUH LITERASI KEUANGAN DAN PENGGUNAAN TEKNOLOGI FINANSIAL (FINTECH) TERHADAP PERILAKU KONSUMTIF PADA GENERASI Z - Yulia Rahmawati; Rendra Gumilar; Sri Hardianti Sartika (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study was to determine the effect of financial literacy and the use of financial technology (fintech) on consumptive behavior in generation Z partially and simultaneously. This research uses quantitative methods. The population in this study were Economics Education Students Class of 2021 and Class of 2022 at Siliwangi University. The sampling technique used was Proportionate Stratified Random Sampling. The data analysis technique used SPSS version 30. The results showed that: 1) There is a significant effect of financial literacy on consumptive behavior with a significance of 0.001 <0.05. 2) There is a significant influence of the use of financial technology (fintech) on consumptive behavior with a significance of <0.001 <0.005. 3) There is a significant influence of financial literacy and the use of financial technology (fintech) on consumptive behavior from the f test value obtained a significance value of <0.001 <0.05.